Case Analysis of Habib Riziq Shihab in Spreading Fake News to Personal Medical Record - Fathu Mukarram (UM Purwokerto Press, 2023)
Riziq shihab lied to the public about himself as if he did not experience covid-19, even though it was known and confirmed that he was positively infected with covid-19. There are 2 problem formulations discussed including: 1) How is the protection of the confidentiality of medical records and personal privacy data in Indonesia? and 2) How did the panel of judges interpret Articles 14 and 15 of Law Number 1 of 1946 in the sentencing of Habib Riziq Shihab? The research method used by the author is the normative juridical method. Literature review that collects primary, secondary and tertiary legal materials to be analyzed in perspective. There are two laws regulated in the Criminal Code in general and the ITE Law in particular. a general and the ITE Law specifically in ensnaring Riziq Shihab.